The Influence of the Jakarta Flight Information Center Medan Sector on Air Traffic Services at Palembang Approach Control Unit - Febby Shandra Pratiwi; Rany Adiliawijaya Putriekapuja; Surya Tri Saputra (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
The aviation industry is a strategic sector that supports both national and international connectivity. One common issue in this sector is the delay in transferring flight information between units, which can lead to potential aircraft conflicts and service delays. The Palembang Air Traffic Service (ATS) Unit under AirNav Indonesia, Palembang Branch, operates at Sultan Mahmud Badaruddin II Airport. Specifically, the Jakarta Flight Information Center (FIC) Medan Sector serves as a provider of Flight Information, Alerting, and Advisory Services within the Flight Information Region (FIR). This study aims to analyze the influence of the Jakarta FIC Medan Sector’s role on the provision of air traffic services at the Palembang Approach Control Service Unit. Using a quantitative approach, data were collected through in-depth interviews, direct observation, and documentation studies. Informants were selected through a saturated sampling technique, consisting of 30 individuals directly involved in coordination between the two units. The results show that coordination, communication, and information support from the Jakarta FIC Medan Sector have not been fully optimized. It can be concluded that enhancing these aspects is essential to improve the efficiency and quality of air traffic services at the Palembang Approach Control Unit